(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
This editorial introduced Volume 5, Special Issue 2 (2026) of the OCEM Journal of Management, Technology and Social Sciences, highlighting selected peer-reviewed papers from the Second International Conference on “Innovation for a Sustainable Future: Advancing Green Technologies and Multidisciplinary Research Trends,” organised by the Oxford College of Engineering and Management (OCEM), Nepal. The conference served as an international platform for researchers, academicians, professionals, policymakers, and industry experts to exchange innovative ideas and multidisciplinary research addressing contemporary challenges in sustainable development. The two-day event brought together participants from six countries and contained eight keynote lectures, two panel discussions, and six parallel technical sessions across diverse thematic areas. The conference promoted scholarly dialogue on green technologies, digital transformation, engineering, management, health sciences, environmental sustainability, education, and the social sciences while strengthening international collaboration through institutional partnerships and research networking. Following a rigorous editorial screening and double-blind peer-review process, fifteen selected high-quality manuscripts were accepted for publication in this special issue. The contributions presented in this volume provide theoretical insights, empirical evidence, and practical recommendations that advance multidisciplinary scholarship and support the achievement of the United Nations Sustainable Development Goals (SDGs). This special issue confirms the journal’s commitment to publishing high-quality, ethical, and open-access research that promotes innovation, international collaboration, and sustainable societal development.